2017
DOI: 10.1002/pc.24532
|View full text |Cite
|
Sign up to set email alerts
|

A study of oriented conductive composites with segregated network structure obtained via solid‐state processing of UHMWPE reactor powder and carbon nanofillers

Abstract: FederationReinforced electrically conductive polymer composites based on ultra-high molecular weight polyethylene reactor powder and filled with various amounts of carbon black, graphite nanopowder, and multiwalled carbon nanotubes were studied. The composites were obtained via compaction of a mechanical mixture of the filler and the polymer reactor powders. This was followed by uniaxial deformation of the material under homogeneous shear conditions. The resulting composites possessed high tensile strength (up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…The layer thickness of 100 nm was taken from the thickness of conductive layer formed around UHMWPE grains in solid-state processed UHMWPE/MWCNT composites with 1% volume fraction of the filler, thoroughly investigated in the previous work of the authors. 14
Figure 3.(a) Volume element constructed for deformation tests and conductance calculations with imitated periodic boundary conditions, where the white dashed square contours the investigated sub-volume (“inner” volume), to which the deformation was applied and conductance of which was calculated later; (b) side view of the volume element; and (c) a close-up view of finite element mesh used in simulations, where blue and red color indicate edges of the matrix cubic elements, and purple indicates truss elements representing the MWCNT segments (dashed arrows symbolize constrains of the MWCNT node by the matrix nodes that are created during the embedding). MWCNT: multi-walled carbon nanotube.
…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The layer thickness of 100 nm was taken from the thickness of conductive layer formed around UHMWPE grains in solid-state processed UHMWPE/MWCNT composites with 1% volume fraction of the filler, thoroughly investigated in the previous work of the authors. 14
Figure 3.(a) Volume element constructed for deformation tests and conductance calculations with imitated periodic boundary conditions, where the white dashed square contours the investigated sub-volume (“inner” volume), to which the deformation was applied and conductance of which was calculated later; (b) side view of the volume element; and (c) a close-up view of finite element mesh used in simulations, where blue and red color indicate edges of the matrix cubic elements, and purple indicates truss elements representing the MWCNT segments (dashed arrows symbolize constrains of the MWCNT node by the matrix nodes that are created during the embedding). MWCNT: multi-walled carbon nanotube.
…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, as it was shown earlier, the presence of filler does not significantly affect the process of strengthening through orientation, making it possible to obtain flexible electroconductive materials with high tensile strength. 14,16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the polymers that received substantial attention in the last few decades is ultrahigh-molecular-weight polyethylene (UHMWPE), which is often used as a base polymer for nanocomposites with segregated structures made of nanosized filler [ 20 , 21 ]. Due to the high viscosity of the UHMWPE melt, a limited number of processing methods are available for this type of polymer.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the presence of a filler even in a very high amount does not significantly affect the process of orientation, making it possible to obtain strong and highly flexible electroconductive materials. Nanocomposites based on this special type of UHMWPE and processed in a solid state via compression molding are characterized by an extreme segregation of the filler and by very low values of the percolation threshold [ 20 , 23 ] in comparison to the hot-molded nanocomposites. In the case of solid-state processing of polymer and MWCNT powders, since polymer melting is not involved, MWCNTs only cover polymer powder particles, mostly not penetrating their volume.…”
Section: Introductionmentioning
confidence: 99%